THE EFFECT OF FRICTION FORCE IN ELIMINATING NON-UNIFORMITY OF THREADS IN THE THREAD FORMATION ZONE - Djumabayev G. X. (European Science Publishing, 2024)
The friction force in the thread formation zone has been studied in relation to the rigidity of the cylinder and threads, as well as their deformation equations and graphs. The dependence of the thread's stretching deformation on the wrap angle, the radii of the second cylinder, the density, and the thickness of the thread in the compression zone has also been analyzed, ensuring uniform elongation as a result of stretching.
Keywords: Friction force, Thread formation, stretching deformation, Cylinder radius, Uniform stretching, Wrap angle.